Housing benefit: slow on the take-up?. Issue 1 (2nd January 2016) - Gibb, Kenneth
Abstract : Housing benefit (HB) plays a pivotal dual role within both the income maintenance system for the UK and in terms subsidising housing for lower income households. But as a means-tested benefit open to both social and private tenants, it has significantly less than 100% take-up on both caseload (eligible tenants) and expenditure levels. Estimates suggest that £2.5 billion is unclaimed annually. This paper sets out how the HB system works and sets the argument in the context of the fundamental welfare reforms introduced and underway since 2010. The paper examines the literature on take-up and recent data on HB take-up before exploring the possible policy responses that might address the shortfall.